A CASE OF BULL DOG FETAL MONSTER IN A DEONI COW - KUMBHAR, U B; PATIL, A D; RAGHUWANSHI, D S; THORAT, KANCHAN (The Indian Journal of Animal Reproduction, 2011)
Dystokia due to Bull dog fetal monster in a Deoni cow is reported.